The Moderating Effect of the Presence of Female Executives on the Relationship Between Accounting Conservatism and Cash Holdings - Chaieb, Souad (International Journal of Accounting and Financial Reporting, 2021)
This paper aims to providing evidence for a relationship that could be established between accounting conservatism and cash holdings and to integrating the moderating effect of the presence of women directors on this relationship. The study was carried out on a sample of 100 French companies listed in the SBF120 index over a 5 year period. In general, the results show that the effect of accounting conservatism on the holding of liquidity is positive and significant and that the role of female administrators reinforces this relationship.